Perancangan Interior One Stop Fitness di Surabaya - Ongko, Chelsya (Intra, 2017)
Fitness is one of the lifestyle trends for exercise. The density of activities in modern times makes people looking for practicality in every aspect of their life. It starts by consuming junk foods, unable to do exercise and other unhealthy lifestyles, which will bring bad impact for their health. This condition can be handled by making One-Stop Fitness that has various supporting facilities in one building. Busyness also had an impact on the lack of time to exercise. One Stop Fitness design is made for providing various support facilities to give practicality in exercising for its users. The designed facilities include reception area, cafe, massage room, sports shop, fitness area, yoga area, aerobics area, RPM area and dressing room.